Coercive Control Between Intimate Partners: An Application to Nonfatal Strangulation - Stansfield, Richard (Journal of interpersonal violence, 2021)
Nonfatal strangulation between intimate partners represents an extreme controlling form of violent behavior, increasing the risk that intimate partner violence (IPV) becomes lethal. Guided by Dutton and Goodman’s conceptualization of coercive control, the present research explored the relation between death threats and subsequent nonfatal strangulation to amplify the credibility of those threats, using a large sample of IPV perpetrators (n = 6,488). Logistic regression analyses determined the relation between overt threats to a partner’s life during an initial incident arrest and subsequent nonfatal strangulation postincident arrest, accounting for perpetrator characteristics and assessed risk. Results showed the highly gendered nature of this violent behavior, noting that men were significantly more likely than women to persist in nonfatal strangulation. Given the potential lethality of this violent behavior, the analysis also explored whether treatment service recommendations (family violence education, counseling, and mental health evaluation) mitigate these patterns. These preliminary findings support the further exploration of treatment and intervention efforts for reducing nonfatal strangulation.